The efficacy of combining low-level laser therapy with oral motor exercises in patients with temporomandibular disorders (pilot study) - Alqahtani, Ali M.; Almohaya, Mai S.; Al Torairi, Nezar S.; Otaibi, Lubna M. Al (International Journal of Clinical Trials, 2023)
Background: The term temporomandibular disorders (TMDs) is used for clinical signs and symptoms affecting the masticatory muscles, temporomandibular joints (TMJs) and associated structures or both. TMDs may present clinically with facial pain in the region of the TMJs and/or muscles of mastication, limitation in mouth opening, and TMJ clicking during mastication. Treatment of TMDs includes occlusal splints, drug therapy, physiotherapy, auriculotherapy and low-level laser therapy (LLLT). Methods: Ten patients with TMD were recruited from the Oral Medicine clinics at Prince Sultan Military Medical City. The participants were randomly allocated into two equal groups. All participants attended a total of eight laser treatment sessions using a 940 nm diode laser. The deep-tissue laser hand-piece was applied perpendicular to the Temporalis muscle, Masseter muscle and TMJ region bilaterally. Patients in the second group attended physiotherapy sessions in addition to the laser sessions. Participants were evaluated for range of mandibular movement, pain, and tenderness to palpation before treatment, one-week post-treatment, and thirty days after treatment completion. Results: This study, being a pilot study, was conducted in a comparatively small number of patients. It allowed for the assessment of research feasibility, methodology, limitations, and preliminary outcomes. Moreover, variations in the response to treatment were observed between the two groups, with results of this study supporting previous findings that LLLT is an effective treatment for TMD symptoms, tenderness to palpation, as well as improving jaw functional behavior. Conclusions: Therefore, LLLT therapy may be a promising tool for the management of TMD, especially when combined with physiotherapy.